2015
DOI: 10.1002/2014gl062446
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven vertical acceleration of Icelandic crust measured by continuous GPS geodesy

Abstract: Earth's present-day response to enhanced glacial melting resulting from climate change can be measured using Global Positioning System (GPS) technology. We present data from 62 continuously operating GPS instruments in Iceland. Statistically significant upward velocity and accelerations are recorded at 27 GPS stations, predominantly located in the Central Highlands region of Iceland, where present-day thinning of the Iceland ice caps results in velocities of more than 30 mm/yr and uplift accelerations of 1-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Future studies of the relationship between ice cap load variations and magma generation should include the potential feedback effects introduced by tephra deposition and changes in ice surface albedo. Many studies have demonstrated the link between deglaciation, surface uplift, and magma generation [e.g., Jull and McKenzie , ; Pagli and Sigmundsson , ; Schmidt et al ., ], however, no such study has yet included the potential effects of accelerated ice melt due to climate warming [ Compton et al ., ] or the feedback processes introduced by volcanic tephra deposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies of the relationship between ice cap load variations and magma generation should include the potential feedback effects introduced by tephra deposition and changes in ice surface albedo. Many studies have demonstrated the link between deglaciation, surface uplift, and magma generation [e.g., Jull and McKenzie , ; Pagli and Sigmundsson , ; Schmidt et al ., ], however, no such study has yet included the potential effects of accelerated ice melt due to climate warming [ Compton et al ., ] or the feedback processes introduced by volcanic tephra deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Compton et al . [] showed that cGPS stations in Iceland experience measurable uplift accelerations in the vertical coordinate component. Rather than simultaneously incorporating parameters for initial offsets, velocities, and accelerations in our ice mass inversion scheme, we instead estimated these parameters and used these estimates to reduce the time series such that the residuals exhibit zero mean quasiperiodic motions without secular trends.…”
Section: Cgps Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the GIA‐uncorrected GPS velocities in 1994–2003 were compared with GIA‐corrected velocities in 2003–2010 (Figure d). It is worth noting that the GIA signal in Iceland is time dependent and was significantly faster during 2003–2010 than in 1994–2003 [ Geirsson et al ., ; Compton et al ., ]. Within the uncertainty limits, GIA‐uncorrected 1994–2003 and corrected 2003–2010 velocities are fairly similar and both follow the model curve that results in ~4 mm yr −1 subsidence at the rift center (Figure e).…”
Section: Geodetic Datamentioning
confidence: 97%
“…However, this model is based on InSAR and GPS observations mostly prior to our study period. It also does not account for the observed relatively rapid acceleration of GIA with time [ Compton et al , ]. We find that it underestimates the horizontal and vertical GIA signal in our data.…”
Section: Modelingmentioning
confidence: 99%